Geopolitics of ports: Factoring Iran in India's counterbalancing strategy for "Sino-Pak Axis". Issue 2 (July 2019) - Singh, Sandeep; Singh, Bawa
The article offers an assessment of Iran's role in India's foreign policy calculations vis-à-vis Sino-Pak axis. The changing geopolitical and geostrategic dynamics in the post-Cold War era have brought about new possibilities and opportunities in the Eurasian space. Given the geographical conditions and re-emergence of geopolitical competition, regional connectivity through ports has taken a pivotal position in bilateral and multilateral engagements. Therefore, the port geopolitics has become a buzzword in the regional connectivity. India has many geopolitical, geostrategic and geo-economic interests in the Eurasian region. However, the potential has not been realized yet due to the lack of geographical connectivity. In the backdrop of emerging Sino-Pak axis, their moves and countermoves have been limiting India's multilateral interests including the connectivity across the Eurasian region. In these matrices, Iran's Chabahar Port due to its strategic location has become a crucial enabler for India. However, Iran has offered investment opportunities even to China and Pakistan in the same project. The existing enmities/competition between India and China-Pakistan has made it difficult for New Delhi to convert the proposed project of Chabahar Port into reality. Against this background, the article would try to give answers to these questions; what are the regional dynamics regarding the Sino-Pak axis to block India's connectivity with the Eurasian region? And how Iran's Chabahar Port can be a helping factor in India's counterbalancing strategy for Sino-Pak axis?